Liposomal Resveratrol and/or Carvedilol Attenuate Doxorubicin-Induced Cardiotoxicity by Modulating Inflammation, Oxidative Stress and S100A1 in Rats - Abeer M. Alanazi; Laila Fadda; Ahlam Alhusaini; Rehab Ahmad; Iman H. Hasan; Ayman M. Mahmoud (MDPI AG, 2020)
Doxorubicin (DOX) is a cytotoxic anthracycline antibiotic and one of the important chemotherapeutic agents for different types of cancers. DOX treatment is associated with adverse effects, particularly cardiac dysfunction. This study examined the cardioprotective effects of carvedilol (CAR) and/or resveratrol (RES) and liposomal RES (LIPO-RES) against DOX-induced cardiomyopathy, pointing to their modulatory effect on oxidative stress, inflammation, S100A1 and sarco/endoplasmic reticulum calcium ATPase2a (SERCA2a). Rats received CAR (30 mg/kg) and/or RES (20 mg/kg) or LIPO-RES (20 mg/kg) for 6 weeks and were challenged with DOX (2 mg/kg) twice per week from week 2 to week 6. DOX-administered rats exhibited a significant increase in serum creatine kinase-MB (CK-MB), troponin-I and lactate dehydrogenase (LDH) along with histological alterations, reflecting cardiac cell injury. Cardiac toll-like receptor 4 (TLR-4), inducible nitric oxide synthase (iNOS), tumor necrosis factor (TNF)-α and interleukin (IL)-6 protein expression were up-regulated, and lipid peroxidation was increased in DOX-administered rats. Treatment with CAR, RES or LIPO-RES as well as their alternative combinations ameliorated all observed biochemical and histological alterations with the most potent effect exerted by CAR/LIPO-RES. All treatments increased cardiac antioxidants, and the expression of S100A1 and SERCA2a. In conclusion, the present study conferred new evidence on the protective effects of CAR and its combination with either RES or LIPO-RES on DOX-induced inflammation, oxidative stress and calcium dysregulation.